Microbiome-Metabolomics Analysis Reveals the Protection Mechanism of α-Ketoacid on Adenine-Induced Chronic Kidney Disease in Rats - Mo, Yenan; Sun, Huang; Zhang, Lei; Geng, Wenjia; Wang, Lixin; Zou, Chuan; Wu, Yuchi; Ji, Chunlan; Liu, Xusheng; Lu, Zhaoyu (Frontiers in Pharmacology, 2021)
Objectives: As nitrogen-free precursors of corresponding essential amino, α-ketoacid have been widely prescribed to end-stage renal disease patients together with a low protein diet (LPD). However, the impact of α-ketoacid on intestinal microbiota in chronic kidney disease (CKD) individuals is unknown. The study aims at investigating the variation in the intestinal microbiota and metabolic profile in response to α-ketoacid treatment in an adenine-induced CKD rat model. Design: Rats in the treatment groups were given solution of compound α-ketoacid tablets. At the end of the study, blood, feces, colon tissues and kidney tissues were collected and processed for biochemical analyses, histological and western blot analyses, 16S rRNA sequence and untargeted metabolomic analyses. Results: α-Ketoacid treatment reduced serum creatinine, blood urea nitrogen and 24h urine protein, and alleviated tubular atrophy, glomerulosclerosis and interstitial fibrosis in adenine-induced CKD rats. Moreover, α-ketoacid significantly improved intestinal barrier and increased the abundance of Methanobrevibacter, Akkermansia, Blautia and Anaerositipes while reduced the abundance of Anaerovorax and Coprococcus_3 at the genus level. In addition, our results also demonstrated that α-ketoacid significantly reduced the concentrations of indoxyl sulfate, betaine, choline and cholesterol. Spearman’s correlation analysis revealed that that the abundance of Coprococcus_3 was positively correlated with serum level of betaine, trimethylamine N-oxide, indoxyl sulfate, cholic acid and deoxycholic acid. Conclusion: α-Ketoacid has a reno-protective effect against adenine-induced CKD, which may be mediated regulation of serum metabolic profiles via affecting intestinal microbial community.